2019
DOI: 10.1039/c8cp06209a
|View full text |Cite
|
Sign up to set email alerts
|

Carrier dynamics in highly excited TlInS2: evidence of 2D electron–hole charge separation at parallel layers

Abstract: Imprinted transient grating fringes in TlInS2 are attributed to new crystal phase formed by 2D electron–hole charge separation on local layers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 56 publications
0
8
0
2
Order By: Relevance
“…In conjunction with previously known sequential phase transitions occurring at low temperatures, extensively studied during last decades [1,3,4], recent investigation indicated electro-optical metastable transformations if samples were thermo-cycled or kept for a certain period in the external electric fields (see [5] and references therein). Our previous works have shown that Tl-GaSe 2 as well as the equivalent TlInS 2 compound obey phenomena of temporal or permanent photo-darkening (giant Stark effect) after a prolonged intense laser pulse irradiation [6,7]. Moreover, we demonstrated physical evidence that the periodic electron-hole (e-h) charge separation on the layer plain occurs at any excitation event by self-charge trapping and a small variation in the band gap [6,7].…”
Section: Introductionmentioning
confidence: 56%
See 2 more Smart Citations
“…In conjunction with previously known sequential phase transitions occurring at low temperatures, extensively studied during last decades [1,3,4], recent investigation indicated electro-optical metastable transformations if samples were thermo-cycled or kept for a certain period in the external electric fields (see [5] and references therein). Our previous works have shown that Tl-GaSe 2 as well as the equivalent TlInS 2 compound obey phenomena of temporal or permanent photo-darkening (giant Stark effect) after a prolonged intense laser pulse irradiation [6,7]. Moreover, we demonstrated physical evidence that the periodic electron-hole (e-h) charge separation on the layer plain occurs at any excitation event by self-charge trapping and a small variation in the band gap [6,7].…”
Section: Introductionmentioning
confidence: 56%
“…Two-dimensional (2D) multi-layered dichalcogenide semiconductor TlGaSe 2 has been known for a long time [1,2]. The compound crystallizes in the monoclinic symmetry group C2/c-C 6 2h with the unit cell parameter a = 10.771 Å, b = 10.772 Å, c = 15.64 Å and the main crystallographic c* axis directed at monoclinic angle β = 100.06°. The unit cell contains 16 atoms positioned on two adjacent layers rotated by 90° angle in (100) plain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Интерпретация этих данных как пространственной модуляции времени жизни неравновесных носителей, по сути, не отличается от предлагаемой -пространственной модуляции заполнения ЦЛЗ или модуляции потенциального рельефа кристалла. Исследования динамики краевой люминесценции монокристалла TlInS 2 [20], изоструктурного TlGaSe 2 также свидетельствуют о межслоевом разделении свободных электронов и дырок. Однако предложенная авторами [20] модель, основанная на образовании протяженных дефектов, в частности нарушений последовательности чередования слоев, не объясняет формирование электрической неоднородности кристалла.…”
Section: обсуждение результатовunclassified
“…Исследования динамики краевой люминесценции монокристалла TlInS 2 [20], изоструктурного TlGaSe 2 также свидетельствуют о межслоевом разделении свободных электронов и дырок. Однако предложенная авторами [20] модель, основанная на образовании протяженных дефектов, в частности нарушений последовательности чередования слоев, не объясняет формирование электрической неоднородности кристалла. Действительно, само по себе образование дефекта или ЦЛЗ, изменение его зарядового состояния не ведет к нарушению локальной электронейтральности кристалла, для чего требуется действие сторонних сил, т. е. сил не электрической природы.…”
Section: обсуждение результатовunclassified